SNPs identified by GWAS affect asthma risk through DNA methylation and expression of cis-genes in airway epithelium. Issue 4 (2nd April 2020) - Kim, Soyeon; Forno, Erick; Yan, Qi; Jiang, Yale; Zhang, Rong; Boutaoui, Nadia; Acosta-Pérez, Edna; Canino, Glorisa; Chen, Wei; Celedón, Juan C.
Over the past 12 years, many genome-wide association studies (GWAS) have been conducted to identify susceptibility variants for asthma [1–5]. The Trans-National Asthma Genetic Consortium (TAGC) recently conducted a large meta-analysis of GWAS [3], identifying 878 single nucleotide polymorphisms (SNPs) associated with asthma at 18 loci. The mechanisms underlying such associations are largely unknown but may include effects on gene expression that alter airway epithelial integrity and function. Many asthma-susceptibility SNPs are associated with expression of distant cis-genes in airway epithelium (AE) through DNA methylation. Over 40% of the genes whose expression in AE is associated with such SNPs are differentially expressed in atopic asthma. http://bit.ly/2L1rnIk